Response of rumen bacterial diversity and fermentation parameters in beef cattle to diets containing supplemental daidzein - Xiang H. Zhao; Shan Zhou; Lin B. Bao; Xiao Z. Song; Ke H. Ouyang; Lan J. Xu; Ke Pan; Chan J. Liu; Ming R. Qu (Italian Journal of Animal Science, 2018)
An experiment was conducted to determine the effects of soy isoflavone daidzein on ruminal fermentation, microbial protein synthesis and rumen bacterial community in beef cattle. Six rumen-cannulated adult beef cattle were assigned to three blocks according to similar body weight in a randomised block design, with two cattle each block. Each block randomly received one of the two dietary treatments: control (basal concentrate) and daidzein (supplementation with 500 mg daidzein/kg basal concentrate). High-throughput sequencing data showed that supplemental daidzein increased the relative abundance of bacteria belonging to phylum Bacteroidetes (p = .050), but reduced and tended to reduce the relative abundance of phylum Spirochaetae (p = .030) and Firmicutes (p = .080). At the genus level, the relative abundance of Prevotella (p = .036), RC9_gut_group (p = .019), Succinivibrio (p = .093) and Ruminobacter (p = .085) were increased or tended to be increased by daidzein supplementation. However, supplemental daidzein reduced or tended to reduce some uncultured and unclassified bacteria genus belonging to Ruminococcaceae (p = .028), Prevotellaceae (p = .088) and Lachnospiraceae (p = .068). The ruminal pH (p = .023) and ammonia-N (p = .031) concentration were lower in the daidzein group than in the control group, but the daidzein group tended to have greater ruminal total VFA (p = .063) concentration. Supplemental daidzein increased urinary excretion of allantoin (p = .005) and total purine derivatives (p = .007). Current results suggest that supplemental daidzein can affect ruminal fermentation by changing ruminal microbial community, increase the production of VFA and enhance microbial protein synthesis in the rumen, showing the potential of daidzein for improving ruminal fermentation in beef cattle.